Anxiety and the Use of Alcohol‐Related Protective Behavioral Strategies. Issue 1 (April 2015) - Napper, Lucy E.; LaBrie, Joseph W.; Hummer, Justin F.
<x xml:space="preserve">Abstract</x> Protective behavioral strategies (PBS) are useful skills for reducing the negative consequences of alcohol. The moderating effects of anxiety on the relationship between 3 different types of PBS and negative consequences were examined among students accessing college counseling services. Results revealed a significant interaction between anxiety and strategies while drinking, suggesting that these simple strategies may be particularly beneficial among students who drink heavily and experience high levels of anxiety. Implications for counseling centers are discussed.